Trends in hepatitis A research indexed in the Web of Science: a bibliometric analysis over the period from 1985 to 2019 - Tauseef Ahmad; Manal Abdulaziz Murad; Saima Nasir; Taha Hussein Musa; Mukhtiar Baig; Jin Hui (Taylor & Francis Group, 2021)
Objective A bibliometric analysis was conducted to build an all-inclusive view of the status of research on hepatitis A virus (HAV) for facilitating researchers, health professionals, and policymakers to understand the characteristics of research output in this particular domain. Methods A comprehensive search was conducted in the Web of Science database. The obtained data were exported into Microsoft Excel 2019, OriginPro 2018 and VOSviewer software for windows. Results From 1985 to 2019, a total of 5,950 studies on HAV were published, with an overall h-index of 105, and 90,350 total citations. The most cited article on HAV was "Classification of chronic viral hepatitis: a need for reassessment" authored by Scheuer in the Journal of Hepatology with a total of 1,121 citations. The most cited article on HAV vaccine was "A controlled trial of a formalin-inactivated hepatitis A vaccine in healthy children" by Werzberger et al. in the New England Journal of Medicine with 401 citations. The most frequent year of publication was 2019 (n = 250). The largest number of studies were funded by the United States Department of Health Human Services (n = 199). The organization with the highest number of publications was the United States Centers for Disease Control and Prevention (n = 228). The United State of America (n = 1,500) was the country with the most publications. 'Vaccine' was the leading journal with 299 publications. Conclusions The highest numbers of studies were published in developed countries. There is a clear need for interdisciplinary research approaches to evaluate and intervene in HAV endemic areas.